Manganês no solo, sua avaliação e toxidez de manganês em soja - Rosolem, Ciro Antonio [UNESP]; Bessa, M. A.; Doamaral, P. G.; Pereira, HFM (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1992)
Two experiments were carried out in pots with a Dusky Latossol showing a 15% base saturation. In the first experiment dolomitic limestone was applied to reach 45, 60, 75 and 90% of base saturation. In the second, MnSO4 was applied in rates of 30, 60, 90 and 120 ppm,and base saturation was raised to 70%.Soybean plants cv. IAC-9 were grown up to R6, when dry matter production and manganese accumulation were evaluated. Soybean responded to liming up to 60% base saturation, as Mn availability and evantualy Mn absorption were decreased to non-toxic levels. Mn applied to a reclamed soil up to 120 ppm was not enough to cause toxicity to soybean cv IAC-9. All of the chemical extractors (Ammonium Acetate, DTA, Mehlich and H2SO4) showed modification in Mn availabity in soil but were not definitely related to Mn absorption and dry matter production.

Foram conduzidos dois experimentos em vasos contendo um Latossolo Roxo Distrófico com saturação em bases de 15%. No primeiro experimento foi feita calagem para atingir 45, 60, 75 e 90% de saturação em bases. No segundo ensaio, foram aplicados 30, 60, 90 e 120 ppm de Mn, na forma de MnSO4, no solo corrigido para 70% de saturação em bases. A soja (Glycine max (L) Merr., cv. IAC-9) foi cultivada até R6, quando foi colhida. Foi observada resposta significante da planta à calagem, com aumentos de produção até 60% de saturação em bases. O Mn aplicado não foi suficiente para causar toxidez na soja cv. IAC-9, no solo corrigido. Todos os extratores (acetato de amônio, DTPA, Mehlich a H2SO4) mostraram modificação do Mn trocável do solo, mas a falta de correlação com o Mn absorvido e produção de matéria seca não recomendam sua utilização generalizada.
Soil manganese, its determination, and manganese toxicity in soybeans
Keywords: MINERAL NUTRITION; FOLIAR DIAGNOSIS